Contemporary Wayang Stories in Enhancing Cognitive and Skills of Children in Maintaining Dental and Oral Health - Irma HY Siregar; Wiworo Haryani; Salsabella Wanda Chaerunnnisa (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
The prevalence of dental caries in children is still relatively high in Indonesia. One of the causes is neglect of oral and dental health maintenance. The school dental health business Program carried out to overcome this has not covered all elementary schools in Indonesia. Given the importance of maintaining children's dental and oral health, improving children's dental health promotion programs at school is necessary. Community service has been carried out at MI Al Khaeriyah, Jabungan Semarang city is a promotive program that aims to improve oral hygiene and children's knowledge in maintaining their dental health. Promotional efforts were carried out in packages consisting of fairy tales, interactive questions and answers, demonstrations, and mass brushing of teeth for 42 students in grades 1-6 elementary school. The results showed an increase in knowledge, both to 93% and followed by an increase in dental and oral hygiene criteria by 81%. Counseling in the form of fairy tales, interactive questions and answers, demonstrations, and mass tooth-brushes can motivate students to behave positively in maintaining healthy teeth every day. Promotive actions in children need to be increased and implemented on an ongoing basis to maintain positive behavior, reduce the prevalence rate of caries in the future, and support existing school dental health business programs.